Scottish Criminal Evidence Law : Current Developments and Future Trends. - Duff, Peter (Edinburgh University Press, 2018)
First full-scale thematic analysis of Pina Bausch's Tanztheater, critically evaluating the impact of modernist theatre on her choreographic method.